EPG5 Variants with Modest Functional Impact Result in an Ameliorated and Primarily Neurological Phenotype in a 3.5-Year-Old Patient with Vici Syndrome - Kane, Megan S.; Zhao, Jia; Muskett, Julie; Diplock, Amelia; Srivastava, Siddharth; Hauser, Natalie; Deeken, John F.; Niederhuber, John E.; Smith, Wendy E.; Vilboux, Thierry; Ebrahimi-Fakhari, Darius (Neuropediatrics, 2019)
Congenital disorders of autophagy are multisystem disorders with significant neurological involvement. Ectopic p-granules protein 5 (EPG5)-associated Vici syndrome is a prototypical congenital disorder of autophagy and presents with the cardinal features of agenesis of the corpus callosum, cataracts, cardiomyopathy, immunodeficiency, and oculocutaneous hypopigmentation. The majority of EPG5 variants leading to Vici syndrome are null alleles with only a few missense variants published to date. Here we report a 3.5-year-old male with compound heterozygous EPG5 variants [NM_020964.2: c.772G > T/c.5943–9_5943–5del]. His clinical presentation deviates notably from classic Vici syndrome with a lack of hypopigmentation, cataracts, immunodeficiency, cardiomyopathy, or failure to thrive. Neurological manifestations within the known disease spectrum include early-onset global developmental delay, hypotonia, and postnatal microcephaly. Seizures, hearing loss, or optic nerve atrophy are absent, however. Magnetic resonance imaging demonstrates a thin but fully formed corpus callosum. Based on the ameliorated and primarily neurological phenotype, we hypothesized that the functional impact of the EPG5 variants present would be milder with a higher amount of residual EPG5 expression. Analyses of EPG5 messenger ribonucleic acid (mRNA) in the patient and his parents were performed to examine expression level and splicing; mRNA from a healthy control and a patient with classic Vici syndrome was also included. Aberrant splicing due to the intronic mutation was detected, but no loss of expression. In contrast, we observed a 50% reduction in mRNA expression in classic Vici syndrome patient fibroblasts. These results support a model of disease severity, which correlates to the dosage of EPG5 expression.
Keywords: Vici syndrome; EPG5; autophagy; neurodevelopment; neurodegeneration; gene expression